ANALISIS PENGARUH BERBAGI PENGETAHUAN ORGANISASI TERHADAP KINERJA ORGANISASI: PERAN PEMEDIASI INOVASI ORGANISASI - Fikri, Muhammad Ali (Fakultas Ekonomi dan Bisnis Universitas Ahmad Dahlan, 2017)
The capability of an organization to conduct organizational performance depends on its innovation resources. This capability can be utilized by facilitating organization innovation in the organization. However, organizational innovation activities cannot be happened automatically. Therefore, knowledge sharing plays significant role to encourage organizational innovation particularly in the context of university.The main objective of this study was to analyze the mediation effect of organizational innovation on the impact of organizational knowledge sharing on organizational performance. This study uses the primary data which obtained through the survey by distributing questionnaires. The respondents from this study were employees of university in Province Daerah Istimewa Yogyakarta, who were included in the purposive sampling criteria. The questionnaires were worth to analyze as much as 75 questionnaires from 100 questionnaires. Scale test result of the instruments used in this study meet the standard of validity and reliability analysis.The results of regression analysis of this study indicate that organizational knowledge sharing has a positive effect on organizational performance, organizational knowledge sharing has a positive effect on organizational innovation, and organizational innovation has a positive effect on organizational performance. When the organizational innovation was included as a mediated variable, the effect of organizational knowledge sharing on organizational performance remains positive and significant. This means that the organizational innovation is a partial mediated in the effect of organizational knowledge sharing on organizational performance.